Beta-hydroxy-beta-methylbutyrate supplementation in health and disease: a systematic review of randomized trials - Molfino, Alessio; Gioia, Gianfranco; Rossi Fanelli, Filippo; Muscaritoli, Maurizio (Amino acids, 2013)
Beta-hydroxy-beta-methylbutyrate (HMB), a metabolite of the branched-chain amino acid leucine, is extensively used by athletes and bodybuilders in order to increase strength, muscle mass and exercise performance. We performed a systematic review of the clinical literature on the effectiveness of HMB supplementation in healthy and pathological conditions (i.e. training programs, aging, acute and chronic diseases, and after bariatric surgery). We reviewed all clinical trials indexed in Medline that tested HMB supplementation as well as all the experimental data regarding HMB intracellular mechanisms of action. Search terms included: randomized controlled trials, controlled clinical trials, single- and double-blind method, HMB, proteolytic pathways, muscle atrophy, cachexia, and training. We found out 13 studies testing HMB in healthy young trained subjects, 11 in healthy young untrained subjects, 9 in patients affected by chronic diseases (i.e. cancer, HIV, chronic obstructive pulmonary disease), and 6 in elderly subjects. The indexed studies support that HMB is effective in preventing exercise-related muscle damage in healthy trained and untrained individuals as well as muscle loss during chronic diseases. Most of the selected studies showed the effectiveness of HMB in preventing exercise-related muscle damage in healthy trained and untrained individuals as well as muscle loss during chronic diseases. The usual dose of 3 g/day may be routinely recommended to maintain or improve muscle mass and function in health and disease. The safety profile of HMB is unequivocal. Further, well-designed clinical studies are needed to confirm effectiveness and mode of action of HMB, particularly in pathological conditions.